English Culture, Which Is Conveyed With the Help of Phraseological Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The relevance of the selected topic consists in an integrated approach to the study of universal and national-specific features of the representation of moral and ethical concepts in the phraseological foundation of the language with the use of linguistic and linguistic and cultural analysis. Most proverbs contain figurative meanings based on the generalisation of single facts, which often makes it possible to interpret even proverbs with direct substantiation of meaning more broadly.